Implementation of Role of Card Media in Increasing Students' Narrative Writing Skills in Class IV SD Muhammadiyah 20 Medan - Puspita, T. Winda (Berpusi Publishing, 2023)
The background of this research is the lack of motivation of students in writing stories, the absence of students' interest in learning to write, the absence of learning media, part of writing skills, namely writing essays. This study aims to apply the role card media in improving writing skills on narrative essay material for Indonesian language subjects in class IV SD Muhammadiyah 20 Medan. This study uses a type of PTK (Classroom Action Research). The location of this research was carried out at SD Muhammadiyah 20 Medan on Jalan Gedung Arca Gang Unity. The time of the research was held in February 2022. The subjects of this classroom action research were 23 students in grade IV at SD Muhammadiyah 20 Medan consisting of 9 boys and 14 girls. The object of this research is the application of role-card media in improving narrative essay writing skills in class IV SD Muhammadiyah 20 Medan. Data Collection Instrument using Observation. The data analysis technique used is Teacher Activity Analysis and Student Activity Analysis. The results of the study showed that the results of students' writing skills in the first cycle were 61% complete. The results of students' writing skills in cycle II which were completed were 87%. Analysis of Teacher Activities in cycle I as many as 80 with criteria B (Good). Teacher Activity Analysis In cycle II there were 90 with criteria A (Very Good). Analysis of Student Activities in the first cycle of students who completed as many as 12 students with a percentage of 52.2%. Analysis of students in the second cycle of students who completed as many as 20 students with a percentage of 86.9%.